PML at Mitochondria-Associated Membranes Is Critical for the Repression of Autophagy and Cancer Development - Missiroli, Sonia; Bonora, Massimo; Patergnani, Simone; Poletti, Federica; Perrone, Mariasole; Gafà, Roberta; Magri, Eros; Raimondi, Andrea; Lanza, Giovanni; Tacchetti, Carlo; Kroemer, Guido; Pandolfi, Pier Paolo; et al. (Cell reports (Cambridge), 2016)
The precise molecular mechanisms that coordinate apoptosis and autophagy in cancer remain to be determined. Here, we provide evidence that the tumor suppressor promyelocytic leukemia protein (PML) controls autophagosome formation at mitochondria-associated membranes (MAMs) and, thus, autophagy induction. Our in vitro and in vivo results demonstrate how PML functions as a repressor of autophagy. PML loss promotes tumor development, providing a growth advantage to tumor cells that use autophagy as a cell survival strategy during stress conditions. These findings demonstrate that autophagy inhibition could be paired with a chemotherapeutic agent to develop anticancer strategies for tumors that present PML downregulation. [Display omitted] •PML regulates autophagic processes from ER/MAM domains in a Ca2+-dependent manner•Localization of PML away from the MAMs is dependent on p53•Activation of autophagy by PML depletion promotes survival under stress conditions•Block of autophagy restores the activity of chemotherapy in PML-downregulated tumors Missiroli et al. demonstrate that the tumor suppressor promyelocytic leukemia protein (PML) works as a repressor of autophagy by controlling autophagosome formation at mitochondria-associated membranes (MAMs) in a p53-dependent manner. Together, their studies generate alternative anticancer strategies for tumors that present PML downregulation.